Iowa Birdline update, October 12, 1992 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1992)
Email for the Iowa Birdline update for October 12, 1992. Highlights of the update include sightings of a Red Knot, eleven American Avocets and the continued presence of several Shorebird species. Also included are handwritten notes for the next week's update with sightings of a Lewis's Woodpecker and 28 Pine Siskins. Epson - sheet feed/flatbed